ปฏิกิริยาไฮโดรทรีตติ้งของปาล์มโอเลอินโดยใช้ตัวเร่งปฏิกิริยานิกเกิลโคบอลต์โมลิบดีนัม - ศิรชาติ ชูโต (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The second generation of biodiesel, so-called Green diesel, is diesel from triglycerides using hydrotreating reaction. Green diesel containing mainly normal-alkanes and iso-alkanes was investicated. The reaction was carried out in a trickle-bed reactor to analyse a variation of product yields under the two different catalysts, namely NiMo/Al2O3 and NiCoMo/Al2O3 catalysts. The temperature range was 300°C to 380°C and the pressure range was 450 to 1050 psig at a constant LHSV of 1.0 h−1 and H2/Oil ratio of 500/1 by volume. Experimental results showed that yield of alkanes in hydrotreating reaction increased with the increase of the temperature and the pressure. Moreover, by variation of temperature and pressure, various pathways were selected on oxygen removal step. Increasing the temperature enhanced decarboxylation and decarbonylation pathways, whereas increasing the pressure increased the contribution of hydrodeoxygenation pathway. After hydrotreating reaction of triglycerides to normal-alkanes, the isomerization reactions also have an important role in product properties, since cold flow properties of the products are improved significantly by increase of their i-/n-alkanes ratio. This study evidenced that when NiMo/Al2O3 and NiCoMo/Al2O3 catalysts were used, they produced a similar yield of total alkanes from the hydrotreating reaction under favorable conditions. However, using NiCoMo/Al2O3 catalyst gave a higher isomerization activity than when NiMo/Al2O3 was used. Therefore, products of the reaction carried out with NiCoMo/Al2O3 catalyst containing higher i/n-alkanes had better cold flow properties than those of NiMo/Al2O3 catalyst.